Dual Embeddedness and Entrepreneurial Activities of Second-Generation Ethnic Entrepreneurs: Multiple Case Studies with Vietnamese Entrepreneurs in Germany - Cat My Dang; Aki Harima (My University, 2020)
Dual Embeddedness and Entrepreneurial Activities of Second-Generation Ethnic Entrepreneurs: Multiple Case Studies with Vietnamese Entrepreneurs in Germany
Keywords: Dual embeddedness